Freedom of speech, 1500-1850 - Ingram, Robert G.; Peacey, Jason; Barber, Alex W. (Politics, culture, and society in early modern Britain., 2020)
This collection offers bold reappraisals of the history of freedom of speech in the pre-modern Anglophone world. It addresses the aims and effectiveness of official policies, the thorny issues with which contemporaries grappled and the claims that were and were not made about freedom of expression.